Dietary sulfur amino acid restriction upregulates DICER to confer beneficial effects - Beatriz A. Guerra; Bruna B. Brandão; Silas S. Pinto; Willian G. Salgueiro; Evandro A. De-Souza; Felipe C.G. Reis; Thiago M. Batista; Vanessa Cavalcante-Silva; Vânia D'Almeida; Beatriz A. Castilho; Everardo M. Carneiro; Adam Antebi; et al. (Elsevier, 2019)
Objective: Dietary restriction (DR) improves health and prolongs lifespan in part by upregulating type III endoribonuclease DICER in adipose tissue. In this study, we aimed to specifically test which missing dietary component was responsible for DICER upregulation. Methods: We performed a nutrient screen in mouse preadipocytes and validated the results in vivo using different kinds of dietary interventions in wild type or genetically modified mice and worms, also testing the requirement of DICER on the effects of the diets. Results: We found that sulfur amino acid restriction (i.e., methionine or cysteine) is sufficient to increase Dicer mRNA expression in preadipocytes. Consistently, while DR increases DICER expression in adipose tissue of mice, this effect is blunted by supplementation of the diet with methionine, cysteine, or casein, but not with a lipid or carbohydrate source. Accordingly, dietary methionine or protein restriction mirrors the effects of DR. These changes are associated with alterations in serum adiponectin. We also found that DICER controls and is controlled by adiponectin. In mice, DICER plays a role in methionine restriction-induced upregulation of Ucp1 in adipose tissue. In C. elegans, DR and a model of methionine restriction also promote DICER expression in the intestine (an analog of the adipose tissue) and prolong lifespan in a DICER-dependent manner. Conclusions: We propose an evolutionary conserved mechanism in which dietary sulfur amino acid restriction upregulates DICER levels in adipose tissue leading to beneficial health effects. Keywords: DICER, miRNAs, Dietary restriction, Methionine restriction, Adipose tissue, Aging